Thermodynamics Analysis of an MHD Casson Fluid Flow Through a Rotating Permeable Channel with Slip and Hall Effects - EEGUNJOBI, Adetayo Samuel; MAKINDE, Oluwole Daniel (Engineering Transactions, 2020)
In this paper, the inherent irreversibility in a Casson fluid flow through a rotating permeable microchannel with wall slip and Hall current is investigated. It is assumed that the lower wall is subjected to the velocity slip and fluid injection while the fluid suction occurs at the upper wall. The nonlinear governing equations of momentum and energy balance are obtained, analyzed and solved numerically using the shooting technique together with the Runge-Kutta-Fehlberg integration method. Pertinent results depicting the effects of various embedded thermophysical parameters on the fluid velocity, temperature, skin friction, the Nusselt number, entropy generation rate and the Bejan number are presented graphically and discussed. It is found that the entropy generation rate is enhanced by fluid rotation and velocity slip but lessened with a rise magnetic field intensity. Our results will undoubtedly augment the design and efficient operation of micro-cooling devices, micro-heat exchangers, micropumps and micro-mixing technologies.